Requiem for nature - Terborgh, John, 1936- (Island Press, 1999)
Using Manu National Park in the rain forest of Peru as a standard, the author addresses the multiple threats of civilization to the precarious state of the tropics. He "makes a compelling case that nature can be saved only if good science and strong institutions can be thoughtfully combined."--Jacket